2014
DOI: 10.1128/aem.03784-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence in Bulk Tank Milk and Epidemiology of Campylobacter jejuni in Dairy Herds in Northern Italy

Abstract: . MLST revealed lineages that were common between milk and bovine feces but distinct between cattle and pigeons. In one herd, C. jejuni with the same genotype was isolated repeatedly from bulk milk and a cow with an udder infection. Our results showed a high prevalence of C. jejuni in bulk milk and suggested that udder excretion, in addition to fecal matter, may be a route of bulk milk contamination. MLST analysis indicated that pigeons are probably not relevant for the transmission of C. jejuni to cattle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 33 publications
(44 reference statements)
3
55
1
Order By: Relevance
“…The Campylobacter prevalence observed in our study is relatively low, similar to other studies performed in dairy herds (10,16) but significantly different from that reported by Bianchini et al (7) in an area close to that of our study but involving farms producing milk for different dairy products (i.e., raw or pasteuxized milk and soft or hard cheeses). The lower prevalence found in our study could be related to several factors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The Campylobacter prevalence observed in our study is relatively low, similar to other studies performed in dairy herds (10,16) but significantly different from that reported by Bianchini et al (7) in an area close to that of our study but involving farms producing milk for different dairy products (i.e., raw or pasteuxized milk and soft or hard cheeses). The lower prevalence found in our study could be related to several factors.…”
Section: Discussioncontrasting
confidence: 67%
“…Contaminated water has been implicated as an important source of Campylobacter infection for cattle (7,14,22,25,30). Ellis-Iversen et al (9) found that water trough hygiene was associated with Campylobacter excre tion and that more frequent emptying and cleaning of water troughs reduced the risk of Campylobacter infection in cattle.…”
Section: Figure 2 Intraherd Prevalence Of Thermophilic Campylobactermentioning
confidence: 97%
“…These counts continually yielded acceptable results before and throughout the outbreak investigation. Previous studies have demonstrated a lack of correlation between bacterial counts and presence of pathogens in raw milk (9,10). Mandatory reporting, timely sample collection, pathogen testing, and on-site milk neutralization likely led to C. jejuni detection during this outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…These values are in the range of the mean and maximum levels of contamination predicted by the model in simulation, namely a mean of 0.81 CFU and a maximum of 1789 CFU per serving (210 ml). Bianchini et al (2014) observed that, although rare, a cow with C. jejuni-induced mastitis causes a more constant positivity of bulk milk for C. jejuni. Here too quantitative data on milk shedding by cows with C. jejuni-induced mastitis are few, but two Italian studies reported milk contamination by direct milk excretion from a single animal with a single quarter with C. jejuni-induced mastitis (Cammi et al, 2009;Luini et al, 2009).…”
Section: Discussionmentioning
confidence: 95%